THE IMPORTANCE OF CHARACTER EDUCATION IN THE DIGITAL ERA IN THE HIGHER CLASS OF SDN SANDING 02 - Sylva Nur Hajijah; Nana Hendracipta; Siti Rokmanah (Cakrawala Pedagogik, 2023)
The aim of this research was to find out how influential digital technology is on the character of students. This research is a qualitative research, which was conducted at SDN Sanding 02. The results of the research state that most students are too focused on the digital world, by using cellphone screens freely and using them for a long time, causing children's character to decline and they become lazy in learning. Only 28% or 7/25 students are active in studying and have good character. This digital era has a huge impact on children's personality values. Therefore, character education in the current digital era is very important because we rarely see children playing traditional games like before. Traditional games can foster affection and closeness, and children become more creative when using these traditional games. Therefore, parents, teachers and society play an important role in this problem. So that students as heirs of the nation  have good ethics so they can contribute to creating a just, peaceful and prosperous national life in the digital era.